Managing an Innovative Project in the Transport Industry - Mateusz GONTARZ; Robert JADACH (Communications of International Proceedings, 2021)
Innovation and technology development are the basis for sustainable and inclusive economic growth. Sustainable solutions are needed in the most important sectors of the economy, and road transport is one of them. A tool for implementing such solutions is appropriate to project management. This article aims to discuss and examine the factors for developing such a project. A qualitative study based on a structured literature review was conducted to gather information on the factors influencing the project management method of using intelligent transport in sustainable transport development. This study provides entrepreneurs with knowledge and understanding of the mechanisms for implementing smart solutions in transportation and logistics, enabling them to build a sustainable business network. This study provides insight into the unexplored area of factors influencing the course of projects that support sustainability and create a new business ecosystem. The paper is qualitative and provides ideas for future research.
Keywords: Autonomous Vehicles; Innovation; Project Management; Transport and Logistic.